2016
DOI: 10.1038/ncomms11828
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation of human cortical excitability

Abstract: Prolonged wakefulness alters cortical excitability, which is essential for proper brain function and cognition. However, besides prior wakefulness, brain function and cognition are also affected by circadian rhythmicity. Whether the regulation of cognition involves a circadian impact on cortical excitability is unknown. Here, we assessed cortical excitability from scalp electroencephalography (EEG) responses to transcranial magnetic stimulation in 22 participants during 29 h of wakefulness under constant condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
156
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(172 citation statements)
references
References 69 publications
16
156
0
Order By: Relevance
“…Experimental designs using PSG sleep/wake assessment, cortisol sampling, and next-day measures of neurocognitive functioning (e.g., memory impairment; Keshavan et al, 2010; Li et al, 2016) may also be useful for clarifying risk factors and mediators of relationships between specific sleep/wake disturbances and clinical and functional outcomes in CHR youth. In addition, research has suggested an influence of circadian phase on cortical excitability (i.e., neural reactivity), which in turn impacts cognitive performance (Ly et al, 2016). Cortical excitability, as measured by scalp EEG responses to transcranial magnetic stimulation, may represent another potential mediator of sleep/wake-cognition relationships for future study with CHR adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental designs using PSG sleep/wake assessment, cortisol sampling, and next-day measures of neurocognitive functioning (e.g., memory impairment; Keshavan et al, 2010; Li et al, 2016) may also be useful for clarifying risk factors and mediators of relationships between specific sleep/wake disturbances and clinical and functional outcomes in CHR youth. In addition, research has suggested an influence of circadian phase on cortical excitability (i.e., neural reactivity), which in turn impacts cognitive performance (Ly et al, 2016). Cortical excitability, as measured by scalp EEG responses to transcranial magnetic stimulation, may represent another potential mediator of sleep/wake-cognition relationships for future study with CHR adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Testing after sleep and after sleep deprivation occurred at the same time of day, which is important because cortical excitability changes with time spent awake and with circadian time. Specifically, a recent study measured the amplitude of the TMS-evoked EEG response using a constant routine protocol, which helps unmasking circadian influences [28]. In line with previous sleep deprivation experiments that measured the EEG reaction to TMS [7] or intrinsic measures of cortical excitability [29], it was found that EEG responses were larger at the end as compared to the beginning of 29 hours of continuous wake [28].…”
Section: Introductionmentioning
confidence: 93%
“…All other components, including the P30, did not show significant differences. We only found a non-significant trend for the P30, with a larger amplitude at 1:00PM compared to 10:30AM, which is in line with previous findings of a non-significant increase of P30 amplitude during daytime (Huber et al 2012;Ly et al 2016). The TEP has shown to be reproducible after 1 week ), similar to our observations in three subjects.…”
Section: Discussionsupporting
confidence: 82%
“…This cluster was located left occipitally, just as the two other N100 clusters that turned out to be non-significant after correction. Two earlier reports did not find a significant change of the first large component of the TEP (P30) during daytime (Huber et al 2012;Ly et al 2016). However, these authors did not analyze any other components.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation